2016
DOI: 10.1108/qram-03-2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

ERM adoption in the insurance sector

Abstract: Purpose This paper aims to investigate various institutional pressures driving the adoption and implementation of a new risk management system; enterprise risk management (ERM). Design/methodology/approach The implementation of ERM-related practices is analysed based on an institutional framework and drawing on empirical evidence from multiple sources in ten large/medium-sized insurance companies. This paper focuses on extra-organisational pressures exerted by political, social and economic institutions on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…In other words, their adoption behavior is not driven by reasons to follow professional norms because they have not considered it a norm that must be followed. This finding is in agreement with Shibin et al (2020), Jabbour andAbdel-Kader (2016), andBukhari et al (2020). However, studies in the context of MSMEs on IFRS adoption (Damak-Ayadi et al, 2020), environmental management accounting adoption (Chathurangani & Hemathilake, 2019), tax compliance (Sadress et al, 2019), and internet-based technology adoption (Azam & Quaddus, 2012;Li & Wang, Predicting Islamic Finance Adoption Behavior by MSMEs: … Jurnal Manajemen Bisnis, 2022 | 213 2018) showed a significant role for this normative pressure.…”
Section: Figure 2 Structural Model and Parameter Estimation Resultssupporting
confidence: 72%
“…In other words, their adoption behavior is not driven by reasons to follow professional norms because they have not considered it a norm that must be followed. This finding is in agreement with Shibin et al (2020), Jabbour andAbdel-Kader (2016), andBukhari et al (2020). However, studies in the context of MSMEs on IFRS adoption (Damak-Ayadi et al, 2020), environmental management accounting adoption (Chathurangani & Hemathilake, 2019), tax compliance (Sadress et al, 2019), and internet-based technology adoption (Azam & Quaddus, 2012;Li & Wang, Predicting Islamic Finance Adoption Behavior by MSMEs: … Jurnal Manajemen Bisnis, 2022 | 213 2018) showed a significant role for this normative pressure.…”
Section: Figure 2 Structural Model and Parameter Estimation Resultssupporting
confidence: 72%
“…In terms of corporate characteristics, many studies focus on financial institutions (Jabbour & Abdel-Kader, 2016;Paape & Speklé, 2012). Baxter et al (2013) showed that companies with high Standard & Poor's (S&P) ratings had higher average market responses than did companies with low ratings, which improved ERM quality and governance.…”
Section: Factors That Promote or Obstruct The Introduction Of Ermmentioning
confidence: 99%
“…In addition, the timing of the introduction of ERM may affect the pressure on such regulations and ratings. For example, early adopters of ERM did so due to internal factors such as enhancing financial health and external factors such as improving their ratings (Jabbour & Abdel-Kader, 2016).…”
Section: Factors That Promote or Obstruct The Introduction Of Ermmentioning
confidence: 99%
“…The goal of ERM is to reduce enterprise risk, which in turn would enhance performance. The analysis suggests that the ERM process and culture vary from firm to firm, but facilitating coordination among all departments of a firm remains the central theme (Jabbour & Abdel-Kader, 2016). It can also be noted that the effectiveness of ERM adoption to deliver benefits is mediated by firm-specific characteristics like firm size, firm complexity, encouragement from the board, and the management's willingness to accommodate feedback (Saeidi et al, 2020;Sax & Torp, 2015).…”
Section: Benefits Of Implementing Erm: Evidence From Management Researchmentioning
confidence: 99%